The Relationship between Consumption Patterns and Nutritional Status of Pregnant Women at the Kuta Padang Layung Health Center - Dian Nabillah; Suci Eka Putri; Khairunnas Kharunnas; Itza Mulyani; Adelina Irmayani Lubis (Journal of Nutrition Science, 2024)
Chronic Energy Deficiency (CED) which is defined as a lack of protein and energy consumption is one of the factors causing maternal mortality. The Maternal Mortality Rate (MMR) in the world according to WHO (2019) is 303,000. The maternal mortality rate in ASEAN is 235 per 100,000 live births. The nutritional condition of pregnant women is influenced by several variables, namely food intake, maternal health conditions, gestational age, maternal activity, income, knowledge, cultural food taboos, pregnancy spacing and parity. The purpose of this study was to determine the relationship between eating habits and the nutritional status of pregnant women at the Kuta Padang Layung Health Center. This study describes the correlation using a cross-sectional method using quantitative data, sampling techniques using research instruments, food recall. The results showed that in 2023 the eating habits and nutritional status of pregnant women at the Kuta Padang Layung Health Center had a p-value of 0.000 (p <0.05). For the nutritional status of pregnant women, the majority are in the good category (69.4%), the highest energy intake (65.9%), the highest protein intake (76.5%), the highest carbohydrate intake (67.1%), the highest fat intake (90.6%), and the highest consumption frequency (71.8%) are all in the good category.